2016
DOI: 10.1016/j.jssc.2016.03.037
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic remanence in Yb14−RE MnSb11 (RE=Tb, Dy, Ho) single crystals

Abstract: Single crystals of Yb 14-x RE x MnSb 11 (x ~ 0.1, 0.4; RE = Tb, Dy, Ho) have been prepared as a solid solution by Sn flux reactions of the elements. They crystallize in the Ca 14 AlSb 11 structure type in the I4 1 /acd space group. The RE 3+ preferentially substitutes on the Yb(1) site which is the smallest volume Yb containing polyhedron. In the case of Ho 3+ , a small amount of Ho 3+ also substitutes on the Yb(4) site. The ferromagnetic ordering temperature of Yb 14 MnSb 11 is reduced from 53 K to 41 K as x … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…79 Additionally, the lighter rare earths affect the rate of oxidation, forming a protective oxide surface. 80 In the case of A14-xRExMSb11, the effect of a 3+ rare earth depends upon the RE cation and the element in the A site The amount of RE appears to be limited to x ~ 0.5 in the case of Yb14-xRExMnSb11, 31,[59][60][61][62][63][64]78 however, in the case of Ca14-xRExMnSb11 and Ca14-xRExMnBi11, the amount of x appears to be closer to 1. 65,66 Solid solutions on the M site have focused on Mn-Zn and Mn-Al.…”
Section: A14mpn11 Structure Typementioning
confidence: 98%
See 3 more Smart Citations
“…79 Additionally, the lighter rare earths affect the rate of oxidation, forming a protective oxide surface. 80 In the case of A14-xRExMSb11, the effect of a 3+ rare earth depends upon the RE cation and the element in the A site The amount of RE appears to be limited to x ~ 0.5 in the case of Yb14-xRExMnSb11, 31,[59][60][61][62][63][64]78 however, in the case of Ca14-xRExMnSb11 and Ca14-xRExMnBi11, the amount of x appears to be closer to 1. 65,66 Solid solutions on the M site have focused on Mn-Zn and Mn-Al.…”
Section: A14mpn11 Structure Typementioning
confidence: 98%
“…Site preferences are observed in the occupancy of the cation sites when doping or alloying on the A position. 31,[59][60][61][62][63][64][65][66] The tendency is for smaller atoms to prefer the A1 and A3 sites, and for larger atoms to prefer the A2 and A4 sites. This can be understood through the Hirshfeld surface analysis of chemical bonding.…”
Section: A14mpn11 Structure Typementioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that chemical substitutions and the structure of the tetrahedral cluster, such as bond lengths and bond angles, affect physical properties such as thermoelectric properties. , When Yb sites are substituted by other rare earth elements, different magnetic behavior is observed. Below the ferromagnetic ordering temperature, the saturation moment for Yb 14‑ x RE x MnSb 11 ( RE = La and Ce, 0 < x < 0.7) is the same as Yb 14 MnSb 11 while in Yb 14‑ x RE x MnSb 11 ( RE = Tb, Dy, Ho, and Er, 0 < x < 0.5) it increases with RE amounts. , This indicates that Ce is not ordered while Tb, Ho, and Er are ferromagnetically ordered with Mn moments. Similar alteration of the magnetic properties by RE substitutions has also been observed in La 1– x RE x Co 2 P 2 ( RE = Ce, Pr, Nd, and Sm). , In the case of Yb 14‑ x RE x MnSb 11 , there is additional complexity associated with site specific substitution for the 4 Yb crystallographic sites related to the size of RE 3+ ions and the volumes of Yb sites …”
Section: Introductionmentioning
confidence: 94%